Pemberdayaan Home Industry Melalui Strategi Pengemasan dan Pemasaran Kopi Tradisional di Sukoharjo Pacitan - Yunaita Rahmawati; Rizky Dwi Alfarozi (CV. Adiguna Kertosari, 2022)
The traditional coffee industry is one of the housing businesses engaged in beverage products, this business includes potential assets owned by Ngerjoso hamlet, Sukoharjo Pacitan village. This business was founded in 1991 where the initial goal was to meet the level of public consumptive use of coffee as a beverage ingredient. This business is well known by the public, and in terms of its development potential, it is also quite promising, especially during the COVID-19 pandemic as it is currently seen from the characteristics of the coffee being traded which is able to increase consumer buying interest in a sustainable manner. However, apart from the aspect of potential development, there are several weaknesses due to the lack of proper management of the product branding that is managed. Departing from the potential for business development and product branding management that can be maximized, the researchers decided to carry out service activities by helping to maximize the branding of this traditional coffee business which includes the idea of making product labels, packaging that is more unique and attractive, as well as offline and online marketing. The method used in this service activity uses the ABCD method, namely by extracting assets, developing business potential, and evaluating the success of the activity program. The results of this activity show that the managed business is increasing both in terms of marketing and customer satisfaction with the managed products.